Bağlanma stilleri, sosyal medya bağımlılığı ve koşullu öz-değer arasındaki ilişki - Bayraktar, Mustafa; Balcı Çelik, Seher (Journal of Dependence, 2023)
Objective: The aim of this study is to examine the relationship between three-dimensional attachment styles and contingencies between self-worth with the level of social media addiction in university students. Method: The sample of the research consists of 817 (Female: 507, Male: 310) university students studying at Ondokuz Mayıs University. Three Dimensional Attachment Styles Scale, Contingencies of Self-worth Scale, and Social Media Addiction Scale were used as data collection tools. Results: There is a relationship between the contingencies of self-worth domains and the level of social media addiction in university students, and that physical appearance and getting approval self-worth domains have a mediating effect in the relationship between the anxious/ambivalent attachment style and the level of social media addiction. The independent variable anxious/ambivalent attachment in domains of approval and physical appearance affects the dependent variable social media addiction level. Conclusion: When the values obtained are examined, each unit of change in independent variables causes 2.1 times change in the dependent variable social media addiction level.